PENINGKATAN KUALITAS PENDIDIKAN AGAMA ISLAM MELALUI PENGINTEGRASIAN KURIKULUM MERDEKA DI SMAN 1 2X11 KAYUTANAM KABUPATEN PADANG PARIAMAN - Akhyar, Muaddyl; Nelwati, Sasmi; Khadijah, Khadijah (STIT Al-Ittihadiyah Labuhanbatu Utara, 2023)
This research aims to analyse the implementation of the independent curriculum in Islamic Religious Education learning. How are the stages in the implementation of the independent curriculum in Islamic Education learning at SMAN 1 2X11 Kayutanam. This research was conducted with a qualitative approach. Data collection in this study used observation, interviews, and documentation. The results of this study indicate that the implementation of the independent curriculum at SMAN 1 2X11 Kayutanam is carried out through 4 stages, namely: First, the stage of deepening the basic framework of the Independent Curriculum, where PAI teachers of SMAN 1 2X11 Kayutanam are actively involved in workshops and FGDs for the preparation of TP, ATP and learning modules. The stage of preparing documents, namely the Operational Curriculum for Education Units (KOSP), learning objectives (TP) and the flow of learning objectives (ATP), learning and assessment planning, and project planning to strengthen the profile of Pancasila students (P5). For PAI subjects, the PAI teacher team refers to the Formulation of Learning Outcomes phase E and sets a time allocation of 5 (five) lesson hours for PAI. In the learning implementation phase, PAI subjects consisting of 5 elements are presented with a regular approach with a time allocation of 5 hours per week. At the monitoring and evaluation stage, teachers refer to the learning objectives and then develop indicators of learning achievement based on the essential material.